Pengaruh Penggunaan Sosial Media Terhadap Tingkat Stress pada Remaja Dimasa Pandemi - Fadilla Rahmi Putri; Yolivia Irna Aviani (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The free use of social media in all circles, in the end it can lead to symptoms of stress in adolescents due to the incompatibility of expectations seen on social media with the existing reality. The purpose of this study was to determine the effect of social media use on stress levels in adolescents. The result of this study was the discovery of an increase in stress experienced by adolescent social media users during the pandemic.